STUDI ETNOBOTANI TUMBUHAN OBAT MASYARAKAT KELURAHAN KEMBANG PASEBAN KECAMATAN MERSAM KABUPATEN BATANGHARI - Ade Adriadi; Revis Asra; Siti Solikah (Jurnal Belantara, 2022)
Ethnobotany is a branch of biological sciences that examines the relationship between society and the world of plants. Plants have an important role in the sustainability of life, especially in the utilization as medicinal and food ingredients by a number of traditional in Indonesia. Indonesia has a high biodiversity so that the utilization of biological resources can not be separated from plants that live in nature both intentionally planted and that grow wild in the forest to meet the needs of daily life, for example as a traditional medicine material. Traditional medicine using plants is still found in Jambi Province which has abundant natural wealth, one of which is in Batanghari Regency, Mersam Subdistrict, especially in the Kembang Paseban Village Community. The research aims to find out the types of plants that are used as medicines, the parts used, the way of processing, the benefits of medicinal plants used, the measure of use, cultural value as well as plant parts used as medicinal materials in the community of Kembang Paseban Subdistrict Mersam Batanghari. The research method uses snowball sampling interview method and purposive sampling as well as participatory observation. Based on the results of the study, there are 67 species from 35 families used by the community of Kembang Paseban Village. With the highest value on the leaves as much as 43.01%. The way of processing is brewed, squeezed, kneaded, shredded, sailed to the fire, eaten directly, freshed, and pounded. Boiling medicinal plants is most widely done and considered more effective. Plants with the highest ICS value in the community of Kembang Paseban Village are capo leaves (Blumea balsamifera L.) and keriki leaves (Jatropha curcas L.).